Selective internal radiotherapy alters the profiles of systemic extracellular vesicles in hepatocellular carcinoma - Gylstorff, Severin; Wilke, Vanessa; Kraft, Daniel; Bertrand, Jessica; Pech, Maciej; Haag, Florian; Relja, Borna (International journal of molecular sciences, 2023)
Incidence of hepatocellular carcinoma (HCC) is increasing globally. Radioembolization (RE)/selective internal radiotherapy (SIRT) is a promising treatment for inoperable HCC. RE triggers an immune response, involving extracellular vesicles (EVs) which are crucial for cell communication and tumor development. This study explores EV immune profiles and origins in patients with inoperable HCC before and after SIRT/RE. Blood samples from 50 HCC-patients treated with SIRT/RE were collected before and after therapy to determine cytokines and isolate EVs using size exclusion chromatography. The dynamic range and EV quality required for detecting variations in surface markers were assessed. Thirty-seven EV surface markers were analyzed using flow cytometry and correlated with clinical parameters. Several immunological markers (CD4, CD2, CD40, CD45, CD49e, CD69, CD209-EVs) were present in the circulation of HCC patients. These markers positively correlated with therapy response and survival. Conversely, B cell CD20, endothelial cell CD146, platelet CD49e, and CD41b EV markers negatively correlated with 60-day survival. Elevated levels of IL-6 and IL-8 before therapy correlated negatively with patient survival, coinciding with a positive correlation with CD20-positive EVs. Plasma EVs from HCC patients exhibit immunological, cancer, and coagulation markers, including potential biomarkers (CD4, CD20, CD49e, CD146). These may enhance our understanding of cancer biology and facilitate SIRT therapy monitoring.
Veröffentlicht: 7. August 2023
Gesehen am 28.09.2023